2011
DOI: 10.1007/s12975-011-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony-stimulating Factor for Acute Ischemic Stroke: A Randomized Controlled Trial (STEMTHER)

Abstract: Granulocyte-colony-stimulating factor (G-CSF) functions both as a neuroprotectant and a stimulator of autologous bone marrow stem cell release. Therefore, administration of G-CSF should improve the outcome of stroke. Here, we examine the safety of using G-CSF to treat acute ischemic stroke using a randomized controlled trial involving 20 adult patients presenting with ischemia in the carotid region within 48 h of onset. The experimental group (n = 10) received subcutaneous G-CSF injections (10 mg kg(-1) day(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Only 4 studies 14,22,24,25 reported allocation concealment using sealed opaque envelopes. All trials were double blind to participants and outcome assessors except 3.…”
Section: Study Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Only 4 studies 14,22,24,25 reported allocation concealment using sealed opaque envelopes. All trials were double blind to participants and outcome assessors except 3.…”
Section: Study Qualitymentioning
confidence: 99%
“…Meta-analysis of 6 studies [20][21][22][23]25,27 with 494 patients demonstrated an insignificant difference in SAE (RR, 1.12; 95% CI, .91-1.38; P 5 .28). Six studies 14,[19][20][21][22]27 with 450 patients showed nonsignificant differences in the death of SAE (RR, 1.25; 95% CI, .82-1.91; P 5 .30).…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations